The impact of obesity in cirrhotic patients with septic shock: A retrospective cohort study. (18th December 2017) - Kok, Beverley; Karvellas, Constantine J.; Abraldes, Juan G.; Jalan, Rajiv; Sundaram, Vinay; Gurka, David; Keenan, Sean; Kumar, Aseem; Martinka, Greg; Bookatz, Brian; Wood, Gordon; Kumar, Anand; et al.
Abstract: Background & Aims: The prevalence of obesity in cirrhosis is rising. The impact of obesity in critically ill cirrhotic patients with sepsis/septic shock has not been evaluated. This study aimed to examine the relationship between obesity and mortality in cirrhotic patients admitted to the intensive care unit with septic shock. Methods: A retrospective cohort study of all cirrhotic patients with septic shock (n = 362) and a recorded body mass index (BMI) from an international, multicentre (CATSS) database (1996‐2015) was performed. Patients were classified by BMI as per WHO categories. Primary outcome was in‐hospital mortality. Multivariate logistic regression analyses were carried out to determine independent associations with outcome. Results: In this analysis, mean age was 56.4 years, and 62% were male. Median BMI was 26.3%, and 57.7% were overweight/obese. In‐hospital mortality was 71%. Obese patients were more likely to have comorbidities of cardiac disease, lung disease and diabetes. Compared to survivors (n = 105), non‐survivors (n = 257) had significantly higher MELD and APACHEII scores and higher requirements for renal replacement therapy and mechanical ventilation ( P  < .03 for all). Using multivariable logistic regression, increase in BMI (OR 1.07, P  = .034), time delay to appropriate antimicrobials (OR 1.16 per hour, P  = .003), APACHEII (OR 1.12 per unit, P  = .008) and peak lactate (OR 1.15, P  = .028) were independently associated with in‐hospital mortality. Conclusions: Septic shock in cirrhosis carries a high mortality. Increased BMI is common in critically ill cirrhotic patients and independently associated with increased in‐hospital mortality.